Subcutaneous Implants of a Cholesterol-Triglyceride-Buprenorphine Suspension in Rats. (9th April 2017) - Guarnieri, M.; Brayton, C.; Sarabia-Estrada, R.; Tyler, B.; McKnight, P.; DeTolla, L.
Abstract : A Target Animal Safety protocol was used to examine adverse events in male and female Fischer F344/NTac rats treated with increasing doses of a subcutaneous implant of a lipid suspension of buprenorphine. A single injection of 0.65 mg/kg afforded clinically significant blood levels of drug for 3 days. Chemistry, hematology, coagulation, and urinalysis values with 2- to 10-fold excess doses of the drug-lipid suspension were within normal limits. Histopathology findings were unremarkable. The skin and underlying tissue surrounding the drug injection were unremarkable. Approximately 25% of a cohort of rats given the excess doses of 1.3, 3.9, and 6.5 mg/kg displayed nausea-related behavior consisting of intermittent and limited excess grooming and self-gnawing. These results confirm the safety of cholesterol-triglyceride carrier systems for subcutaneous drug delivery of buprenorphine in laboratory animals and further demonstrate the utility of lipid-based carriers as scaffolds for subcutaneous, long-acting drug therapy.